The Traumatic on Having Marriage to Female Teenagers from Divorce Family - Agus Aprianti (Lingkar Studi Komunikasi (LISKI), 2023)
Adolescents who experience losing their parents due to divorce will face psychological wounds called trauma. The trauma affects how their view marriage in the future. There were 3 adolescent informants who were interviewed using a phenomenological approach. The trauma felt by teenagers is the fear of being abandoned by their partner, the fear of divorce will happen again, the fear of getting domestic violence and the fear of the spouse’s family not accepting the divorced family background. The traumatic experience of their parents getting divorced in the end made them decide not to get married when they grew up. Keywords: Traumatic, Divorce, Teenagers, Family